"I just want to be normal": A qualitative investigation of adolescents' coping goals when dealing with pain related to arthritis and the underlying parent‐adolescent personal models. Issue 3 (28th December 2021) - Ghio, Daniela; Calam, Rachel; Lee, Rebecca Rachael; Cordingley, Lis; Ulph, Fiona; ,
Abstract: The aim of the current study was to examine adolescents' goals when coping with pain and map these goals to the cognitive and emotional profiles of both adolescent and their parent. 17 adolescents (11‐16 years) and their parents participated in a cohort study of Juvenile Idiopathic Arthritis (JIA); the adolescents, took part in a two‐part interview (about their pain perceptions and about a recent pain experience) and the parents completed an open‐ended qualitative survey. The three datasets were analysed following a qualitative framework approach. A coping framework was developed and cognitive and emotional profiles for both adolescent and parent were mapped back to the framework. The overall goal of adolescents was to preserve social identity, by either focusing on maintaining a "normal" lifestyle (sub‐coping goal one) or managing the pain (sub‐coping goal two). Across these two sub‐coping goals, the adolescents held similar cognitive profiles (beliefs about timeline, consequences, control) but different emotional profiles such as feeling fine/happy compared with feeling angry and frustrated. Conversely, the parents' cognitive and emotional profiles were mapped back to the two groups and found that their beliefs were different across the two sub‐coping goals but had similar emotional profiles across the two groups such as worry. Both the adolescents' emotional representations and parental cognitive profiles seem to be related to how the adolescent perceives a pain event, deals with the pain, and the overall coping goal of the adolescent. Findings are suggestive that parental pain beliefs influence the adolescents' pain representations and their coping goals but are also driven by adolescents' emotions. Further work on these potential pathways is needed. Family interventions should be designed, targeting coping goals taking into consideration the importance of emotions for adolescents and parental pain beliefs.